Autism Spectrum Disorders Recent Advances and New Perspectives - Carotenuto, Marco (IntechOpen, 2023)
This book offers innovative constructs of knowledge and reasoning on autistic pathology according to the perspectives offered by functional neuroscience and neuroimaging data and considers new etiological perspectives and therapeutic strategies centered on the child and the family. Written by experts in the field, this book includes sixteen chapters organized into three sections on "Worldwide Epidemiology", "Neural Perspectives and Etiology", and "Therapeutic Strategies".